A RFID Protocol For Detecting The Existence Of A Single RFID Tag By Two RFID Readers - Tan , Aik Theng (2012)
There is a limitation for a RFID reader to read thousands of data provided by RFID tags in a second. Hence, multiple RFID readers configuration is required to help resolving this scenario. In real world applications of RFID system, there will be a lot of configurations for RFID reader and RFID tag such as multiple RFID tag communicate with a RFID reader or vice versa, multiple RFID tag communicate with multiple RFID reader and multiple RFID readers communicate with a single RFID tag. In order to ensure that existing network protocols which developed by previous researchers for communication in RFID system can support in whatever types of RFID tag and RFID reader configuration, a reliability and specific test through these existing network protocols have been introduced in this research work.